Financing risk management to anticipate financial distress in Islamic banks - Riana Afliha Eka Kurnia; Tjiptohadi Sawarjuwono; Sri Herianingrum (Department of Islamic Economics, Islamic University of Indonesia, 2017)
Uncertainty was not only found in conventional banks but also in Islamic banks. Financing risks in Islamic banks can occur because Islamic banks have made some modifications to sharia contracts used for financing to adjust general business of banks environments. Thus Islamic banks, like conventional ones, face risks and business issues. This study discusses how risk management at Bank Islam poses a risk to financial difficulties probability. This study will explain that Islamic banks should establish a risk management system by its functionality and complexity of the banks, and the system provides bank's risk management organization that suits with sharia principle to at least be able to avoid financial distress conditions.